2016
DOI: 10.5815/ijmecs.2016.11.04
|View full text |Cite
|
Sign up to set email alerts
|

On Overcoming Transitional Challenges of First Year Students in Technology-Based Educational Settings

Abstract: Universities in South Africa (SA) are facing several challenges due to the influx of students with diverse backgrounds entering the first year. One of such challenges is the use of technologies for teaching and learning. Institutions in the rural areas are flooded with first year students characterized as under-prepared, educationally underprivileged and had little or no access to computer usage prior to their enrolment. These qualities impedes their transition into the computer-based learning system and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Both institutions are located in socially and historically disadvantaged communities because of the policies of the apartheid government prior to 1994. Owing to their rural location, it was particularly difficult for these universities to suddenly transition from face-toface to online teaching and learning (Mbodila et al 2016). For instance, neither of the communities has an adequate ICT infrastructure able to abruptly support online teaching and learning activities.…”
Section: Methodsmentioning
confidence: 99%
“…Both institutions are located in socially and historically disadvantaged communities because of the policies of the apartheid government prior to 1994. Owing to their rural location, it was particularly difficult for these universities to suddenly transition from face-toface to online teaching and learning (Mbodila et al 2016). For instance, neither of the communities has an adequate ICT infrastructure able to abruptly support online teaching and learning activities.…”
Section: Methodsmentioning
confidence: 99%
“…This problem of transitioning to ICT adoption is also reported in the study by Mbodila et al (2016) who noted that institutions in rural areas of South Africa are flooded with first-year students who are considered to be underprepared and had no access to computers before their enrolment. Also, most students from the rural areas usually lack knowledge of computers when they arrive at the university which accounts for their difficulties when searching for study materials, typesetting their assignments and submitting them online, as they have had no experience in the use of this technology at high school.…”
Section: "Everything Was Difficult I Didn't Know About Blackboard It ...mentioning
confidence: 71%
“…It also offers the means to broaden teachers' experience through interactive collaboration with other education stakeholders around the world . Research has reveals revealed that the use of different approaches offered by ICT enhance not only teaching but also simplify preparation of assessment tools and processing of examination results (Mbodila & Muhandji, 2013). Agbobli (2002) contends that, given the clear goals of education in human life, the use of ICT is a great way for people to achieve the goals.…”
Section: Teacher's Use Of Ict In Teaching and Assessment Of Learningmentioning
confidence: 99%